Sex-related differences in self-efficacy in patients with heart failure: a pooled cross-sectional study of the German Competence Network Heart Failure - Kerwagen, Fabian; Sahiti, Floran; Albert, Judith; Bauser, Maximilian; Morbach, Caroline; Güder, Gülmisal; Frantz, Stefan; Strömberg, Anna; Kerber, Sebastian; Gebhard, Brigitte; Friederich, Hans-Christoph; Müller-Tasch, Thomas; et al. (European journal of cardiovascular nursing, 2024)
To assess the level of self-efficacy in patients with heart failure (HF), identify differences between important subgroups including sex, and identify the determinants of high self-efficacy.This was a pooled cross-sectional analysis of 2030 patients from 4 prospective studies conducted within the German Competence Network Heart Failure. We used the self-efficacy subscale and the overall summary score (OSS) of the Kansas City Cardiomyopathy Questionnaire (KCCQ-23) to assess self-efficacy and health-related quality of life. The cut-off of 75 score points was used for the dichotomization into high (≥75) vs. low (<75) self-efficacy. Depressive symptoms were measured by the Patient Health Questionnaire (PHQ-9). A total of 1615 patients with HF provided complete self-efficacy scores: mean age 66.6 ± 12.3 years and 431 (27%) women. The mean self-efficacy score was 67.5 ± 24.9, with 907 patients (56.2%) showing high self-efficacy and 708 patients (43.8%) showing low self-efficacy. Men had higher self-efficacy scores than women (68.7 ± 24.5 vs. 64.2 ± 26.0; P = 0.001). Multivariable logistic regression identified the KCCQ-OSS [odds ratio (OR) per five-point increase 1.08, 95% confidence interval (CI) 1.04-1.12], female sex (OR 0.72, 95% CI 0.56-0.94), depressive symptoms (OR per three-point increase in PHQ-9 0.90, 95% CI 0.83-0.98), and acute HF (OR 0.46, 95% CI 0.34-0.62) as important predictors of high self-efficacy.In patients with HF, women seemed to exhibit lower self-efficacy than men. Health-related quality of life and psychological well-being were dominant determinants of self-efficacy. Future studies should investigate the role of self-efficacy as a therapeutic target for tailored and sex-specific nursing interventions.